Peran Pendidikan Agama Islam Dalam Menanamkan Sikap Moderasi Beragama Siswa Di SMA Negeri 1 Rejang Lebong - Rahmat Yudhi Septian; Maria Botifar; Deri Wanto (LPPM IAIN Sorong, 2022)
Abstract: SMA Negeri 1 Rejang Lebong is a school which incidentally is a superior public school located right in the heart of the capital city of Rejang Lebong district, of course there are various kinds of people with various ethnicities, customs and beliefs in this education unit. Starting from the indigenous students of Rejang and Lembak as well as descendants of Java, Sunda, Minang, Batak, Chinese, Serawai, and others are in this school. In terms of belief, teachers and students at SMA Negeri 1 Rejang Lebong also believe in the six official religions, namely Islam, Catholicism, Protestantism, Hinduism, Buddhism and Confucianism. Therefore, religious moderation is considered important and needs to be enforced in order to be able to guide the life of the school community in a good direction with a harmonious community structure without hatred and violence. In this journal article, the researcher uses field research with a descriptive qualitative approach with the principal and PAI teacher at SMA Negeri 1 Rejang Lebong as informants in this study. Then structured interview is the technique used in this study and data collection, data display, data reduction and verification or conclusion are data analysis techniques used in this study. SMA Negeri 1 Rejang Lebong has internalized the values ​​of religious moderation in Islamic religious education subjects and integrated them in the development of PAI materials and materials recorded in the PAI learning plan and their implementation has been realized in the PAI learning process.